The applicability of economic models in estimating the economic impacts of tourism in a local economy - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2013)
The economic impacts of tourism have received substantial attention and have been documented by many researchers due to its ability to generate economic benefits to local economy. To date, there is no standard model to estimate economic impact study and most of the studies modify the original model to meet the interest of researchers. This paper aims to discuss the applicability, strength and limitations of four techniques frequently employed in estimating economic impacts of tourism 1) Input-output model, 2) Social Accounting Matrix, 3) Computable General Equilibrium, and 4) Tourism Satellite Account. Next, the rationale of choosing the suitable model to be used in estimating the economic impacts of tourism will be discussed. This paper concluded that IO models are suitable to estimate the economic impacts of tourism in a local economy.